KUALITAS AIR PADA DEPOT AIR MINUM ISI ULANG YANG TERVERIFIKASI DI WILAYAH KERJA PUSKESMAS GROGOL, KABUPATEN SUKOHARJO - Naufal Maulana Wijaya; Yuni Wijayanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2022)
A preliminary study of 10 DAMIUs showed that there were 3 DAMIUs that did not meet the requirements for coliform in the working area of the Grogol Health Center, Sukoharjo Regency. Meanwhile, Grogol District has the highest number of DAMIUs in Sukoharjo Regency, namely 50 DAMIUs consisting of 30 unverified and 20 verified, verified, which has received routine supervision by the Grogol Health Center. Based on 2019 data, diarrhea cases were ranked first in infectious diseases with 4,686 cases. This type of research is quantitative descriptive using a case control. The samples needed in this study were 15 samples as cases and 15 as controls, so that what was needed was 30 DAMIU. DAMIUs were selected randomly, the case group was the unverified DAMIU and the control group was the verified DAMIU. The instruments used in this study were questionnaire sheets and observation sheets.statistical test chi square. The results showed that there was a relationship between the sanitation of the DAM place (p=0.006), the hygiene of the DAM handlers (p=0.001), and supervision with the quality of DAMIU drinking water in the working area of the Grogol Health Center, Sukoharjo Regency. And there is no relationship between the sanitation of DAM equipment (p=0.709) and raw water sources (p=0.063) with the quality of DAMIU drinking water in the working area of the Grogol Health Center, Sukoharjo Regency. The suggestion of this research is to improve the quality of DAMIU drinking water, as well as routine guidance and supervision by health agencies on DAMIU on a regular basis to improve the quality hygiene and sanitation.